Implementation of Straight Motion Learning Using Software Tracker Towards Junior High School Students 'Cognitive Abilities - Erin Wardani; Indrawati Indrawati; Iwan Wicaksono (Pancaran Pendidikan, 2021)
This study aims to determine the effect of using tracker software media on students' cognitive abilities in straight motion material in junior high school. This research is an experimental study with a post-test only control design. The population was tested for homogeneity to obtain samples, namely two classes with homogeneous abilities. Furthermore, learning was carried out using the tracker software media in the experimental class. The students' post-test scores were tested for normality using the Kolmogorov Smirnov test. Furthermore, if the data is normally distributed, it is followed by an independent sample t-test. The results of the analysis using SPSS show that the sig. (2-tailed), namely 0.000 so that it is smaller than 0.05. Based on these results it can be concluded that there is a significant difference in the cognitive abilities of students between the control and experimental classes in learning straight motion.